Sugarcane Ring Spot - Philippe Rott; Jack C. Comstock; Hardev S. Sandhu; Richard N. Raid (EDIS)
Ring spot, caused by the fungus Leptosphariea sacchari, is a disease of sugarcane that has been known to occur in Florida for over 80 years. Ring spot usually affects only the older leaves, and therefore is considered a minor disease. However, correctly identifying the disease in the field can help to reduce unnecessary chemical sprays. This 2-page fact sheet outlines the symptoms and spread of the disease, as well as how to prevent and control Sugarcane Ring Spot. Written by P. Rott, J.C. Comstock, H.S. Sandhu, and R.N. Raid, and published by the Plant Pathology Department, September 2015.